Developing an Object Oriented Model of Critical Success Factors for Clusters: The Linkˆping Information and Communication Technologies Cluster Test-Case - Sam Tavassoli; Dimitrios Tsagdis (European Regional Science Association (ERSA), 2010)
An object oriented model (OOM) of critical success factors (CSFs) for clusters is developed on the basis of an extensive and critical review of the literature. The model is tested, as a proof of concept, in the Linköping information and communication technologies (ICT) cluster, Sweden. The model is flexible, scalable, and open-ended, applying equally to particular clusters as well as to clusters in general. The model aims to act both as a diagnostic tool for CSFs in particular clusters as well as a framework for policy and research in general. The model encompasses some 21 CSFs (e.g. trust, vision, knowledge) that belong or depend on one or more objects (e.g. firms, institutions, entrepreneurs) relevant to a cluster. A Venn diagram is initially developed on the basis of the literature to help delineate the relevant objects and is subsequently translated into the aforementioned model. The testing of the model follows a cluster life-cycle approach and ranks the 21 CSFs in terms of their relevance during different stages in the life-cycle of the Linköping ICT cluster. It is argued that the importance of different CSFs varies throughout a cluster's life-cycle concluding with some relevant policy implications and areas of further research.
Keywords: 330